APA Handbook of Consumer Psychology. 2022
DOI: 10.1037/0000262-027
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of consumer decision making and neuroforecasting.

Abstract: Neuroscience, in recent years, has contributed significantly to a better understanding of how individuals make decisions and how these decisions are influenced by context, states, and individual traits. The past decade has seen the emergence of consumer neuroscience as an academic field of inquiry that applies tools and theories from neuroscience to better understand consumer behavior. These studies have primarily used functional magnetic resonance imaging (fMRI) and electroencephalography (EEG), although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 71 publications
0
5
1
Order By: Relevance
“…In fact, the information that we presented would be mostly unintelligible to untrained eyes, underlining the importance of our sample of professional investors with specific and relevant expertise. While previous studies found a relationship between market-level outcomes and brain responses of naïve participants to simplified stimuli presented out-of-context (7), our study shows that the market can be predicted by brain responses of experts processing comprehensive, realistic information.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…In fact, the information that we presented would be mostly unintelligible to untrained eyes, underlining the importance of our sample of professional investors with specific and relevant expertise. While previous studies found a relationship between market-level outcomes and brain responses of naïve participants to simplified stimuli presented out-of-context (7), our study shows that the market can be predicted by brain responses of experts processing comprehensive, realistic information.…”
Section: Discussioncontrasting
confidence: 91%
“…Whether or not this implies that AIns responses can only be related to short-term market outcomes, or also long-term, remains an open question. The alleged different mechanisms of the brain components investigated here (i.e., NAcc, MPFC, AIns), and their potential for neuroforecasting, deserves more attention (7,8) and further stresses the importance of studying the neurobiology of financial decision-making (20).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations